Identification and validation of mixed anxiety–depression. Issue 14 (8th June 2015) - Hettema, J. M.; Aggen, S. H.; Kubarych, T. S.; Neale, M. C.; Kendler, K. S.
Abstract : Background: Mixed anxiety–depression (MAD) has been under scrutiny to determine its potential place in psychiatric nosology. The current study sought to investigate its prevalence, clinical characteristics, course and potential validators. Method: Restricted latent-class analyses were fit to 12-month self-reports of depression and anxiety symptom criteria in a large population-based sample of twins. Classes were examined across an array of relevant indicators (demographics, co-morbidity, adverse life events, clinical significance and twin concordance). Longitudinal analyses investigated the stability of, and transitions between, these classes for two time periods approximately 1.5 years apart. Results: In all analyses, a class exhibiting levels of MAD symptomatology distinctly above the unaffected subjects yet having low prevalence of either major depression (MD) or generalized anxiety disorder (GAD) was identified. A restricted four-class model, constraining two classes to have no prior disorder history to distinguish residual or recurrent symptoms from new onsets in the last year, provided an interpretable classification: two groups with no prior history that were unaffected or had MAD and two with prior history having relatively low or high symptom levels. Prevalence of MAD was substantial (9–11%), and subjects with MAD differed quantitatively but not qualitatively from those with lifetime MD or GAD across the clinical validators examined. Conclusions: Our findings suggest that MAD is a commonly occurring, identifiable syndromal subtype that warrants further study and consideration for inclusion in future nosologic systems.